An understanding of student’s attitudes towards quran memorization for ctu101: analysis of UITM students' memorization skills - Syaimak Ismail; Nor Iman Nabilah Abu Bakar; Siti Hanisah Sabri; Noor Syahidah Mohamad Noor (International Journal Of Modern Education (IJMOE), 2024)
The practices of Quranic memorisation are increasingly prevalent and significantly prominence in the Muslim community, especially in Malaysia. Thus, the establishment of Tahfiz Model Ulul al-Bab (TMUA) which implemented at national level was initiated by Datuk Seri Idris b. Jusoh in 2014 portrays as an evidential measure as to realize the inspiration of the government to nurture the professional potential huffaz with leadership skill and competent to lead the community. Nevertheless, this effort has extended to the tertiary education especially in public university in Malaysia as to preserve the consistency of Quranic memorization among the students. Correspondingly, University Teknologi Mara (UiTM) also incorporated Quranic memorisation as a requirement task and therefore, must be fulfilled by diploma students taking the Fundamental of Islam course (CTU101). Unfortunately, the reality is that students are often struggling to complete the task, which takes significantly additional time to accomplish the task. Thus, a preliminary study was conducted to understand the attitudes of the students at UiTM Perlis in the implementation of the Quran memorization of selected chapter and to analyse the relationship between attitudes and their educational setting by considering their respective faculties. The study employed quantitative research and adopted convenience sampling techniques through a survey distributed amongst eighty-two students who currently enrolled into CTU101 for the session October 2023/February 2024. The study includes both descriptive and inferential statistics to explore the dependent variable and the differences in term of between three faculties. The research shows that the students demonstrate a positive attitude toward Yasin memorization for CTU101 (M=3.62, SD=0.301). Apparently, the study demonstrates that there is significant relationship between attitudes and their environmental setting from different faculties at the p<.05 level for the three conditions [F (2, 79) = 9.904, p =.000]. Turkey Post-Hoc were later performed to identify and suggests that students from Faculty of Sports and Recreations shows positive inclinations towards task of Yasin memorization for CTU101 in comparison to students from the Faculty of Applied Sciences and the Faculty of Computer Science and Mathematics. Nevertheless, diverse educational environments have had a significant influence on students' views towards memorisation of Yasin, specifically for this study. This study requires remarkable attention from relevant parties to ensure the effectiveness of the subject as to instil Islamic values and improve Quranic skills among the Muslim student in especially in UiTM.